Vulcanian explosion at Soufrière Hills Volcano, Montserrat on March 2004 as revealed by strain data - Linde, Alan T. (2012)
The CALIPSO collaborative volcano monitoring system on the Caribbean island of Montserrat includes observations of strain at depths ∼200 m using Sacks-Evertson strainmeters. Strain data for the March 2004 explosion of the Soufrière Hills Volcano are characterized by large, roughly equal but opposite polarity changes at the two near sites and much smaller changes at a more distant site. The strain amplitudes eliminate a spherical pressure (Mogi-type) source as the sole contributor. The initial changes are followed by smaller recoveries, but with differing relative recovery magnitudes. This dissimilarity requires a minimum of two pressure sources, which we model as a deep spherical pressure source and a shallow dike. The spherical source is fixed at the location derived from data for the massive dome collapse in July 2003. We solve for the best fitting dike plus sphere source combination. The dike geometry is consistent with earlier interpretations of dikes based on GPS data and other lines of evidence.